Detecting outliers and level shifts in time series using Tsay and Balke procedures - Elnas, Calixto Gonzaga (2004)
Abstract (Balke (1993) considers only permanent level changes in evaluating Tsays disturbance search procedure is less effective in detecting permanent level changes. Thus, Balke (1993) suggests a white - noise initialization in the disturbance search procedure is not supported by facts. Hence, this paper attempts to investigate the ability of Tsays disturbance search procedure to detect transient level changes in time series. Based on simulated series with transient level change and permanent level change disturbances, the simulation results indicate that Tsays disturbance search procedure is also not that effective in detecting transient level changes. However, the simulation results also show that for all parameter settings in the transient level change statistics based on an estimated autoregressive (AR) parameter is sensitive to detect transient level changes in certain situation).
"May 2004."
Thesis (M.S. Statistics)--University of the Philippines, Diliman.
Keywords: Time series analysis; Outliers (Statistics).; Stochastic processes; Autoregression (Statistics).